Survey of big-data-analysis-resistant privacy protection - Wei TONG; AOYun-long M; Qing-jun CEHN; Bin-ru WANG; Bao-jia ZHANG; Sheng ZHONG (网络与信息安全学报)
Privacy protection plays a significant role in big data era for data sharing and analysis.Traditional privacy protection approaches may not apply well for big data scenarios,because there may exist deep associations which can also cause privacy leakages.Therefore,privacy protection mechanisms that can defend against big data analysis is needed.A survey on related works was conducted,and the previous works were classified into three categories:privacy protection for massive high-dimensional heterogeneous data,location privacy protection and privacy protec-tion with enhanced utility.Then,the works in this area by COSEC group from nanjing university were introduced.At last,the privacy protection against big data analysis which was important and forward-looking was concluded,and the possible directions in this research area were introduced.